Relationships between glomerular filtration rate and HRV/EEG parameters - Ruzhylo, Sofiya; Popovych, Dariya; Duzhar, Viktor; Żukow, Xawery; Zakalyak, Nataliya; Kovalchuk, Halyna; Rohalya, Yuriy; Masnyi, Oleg (Journal of Education, Health and Sport, 2024)
Background. Sympathetic outflow may be capable of selectively increasing or decreasing glomerular capillary pressure and hence glomerular filtration rate (GFR) by differentially activating separate populations of renal nerves. Sympathetic outflow to the kidney is regulated by major cortical, brainstem and medullary areas. The purpose of this study is to find out the relationship between GFR and HRV/EEG parameters as markers of the neural regulation of the kidney. Materials and Methods. The object of observations were 10 men aged 37-69 years without clinical diagnosis tested twice with 7-days interval. The rate of glomerular filtration was calculated according to endogenous creatinine clearance and the Cockcroft & Gault formula. The state of the autonomic nervous system was assessed by the HRV method. Simultaneosly qEEG recorded. Results. For the sample as a whole, a weak (r=0.396; p>0.05) correlation was found between HRV-marker of sympathetic tone and GFR. However, two clusters of individuals can be distinguished: with a strong correlation (r=0.852; n=12) and its complete absence (n=8). The qEEG method revealed neural structures generating delta and theta rhythms that upregulate GFR, and generating beta rhythm that downregulate GFR. The regression model, which includes 16 EEG parameters, allows estimating GFR with a standard error of 3,4 mL/min. Conclusion. Glomerular filtration rate is subject to the modulatory regulatory influence of the nervous system and can be estimated with high accuracy by EEG parameters.